2020
DOI: 10.1063/10.0000705
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of atomic and molecular species in carbon cellular structures (Review article)

Abstract: The paper presents a brief review of the recent developments in the field of absorption of atomic and molecular species in carbon cellular structures. Such absorbing objects can be distinctly recognized among a large family of carbon porous materials owing to potential and already observed in experiments very high capacity to soak and to keep inside different substances, which at usual conditions outside the porous matrices may often stay only in a gaseous form. High capacity filling is attained owing to singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 104 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…CHs already demonstrated high capturing ability with respect to different gases including CO 2 . 7,8,[11][12][13] In our preliminary research, 13 we have found that the CO 2 uptake in CHs is very strong and the complete desorption of carbon dioxide captured in the carbon honeycomb matrix does not occur, even at high enough temperatures. This means that CHs used as membranes are very promising materials for CO 2 capturing.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…CHs already demonstrated high capturing ability with respect to different gases including CO 2 . 7,8,[11][12][13] In our preliminary research, 13 we have found that the CO 2 uptake in CHs is very strong and the complete desorption of carbon dioxide captured in the carbon honeycomb matrix does not occur, even at high enough temperatures. This means that CHs used as membranes are very promising materials for CO 2 capturing.…”
Section: Introductionmentioning
confidence: 88%
“…In order to study any gas sorption in CHs, we developed and tested the specific procedure, enabled us to fill nearly fully all available positions inside CHs. 7,8,[10][11][12] In this method, we first make deposition of gases at low temperatures below the known gas sublimation points, and then heat gradually our condensates till the temperatures 2-3 degrees lower these points and keep deposited gases at these temperatures for several minutes monitoring the electron diffraction patterns. Typically, the well-defined peaks from polycrystalline gas deposits disappear, but distinct residual signals left showing that some kind of composites based on CHs with sorbed gases form.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These graphene nanoribbons form the "walls" of periodic hexagonal cells in a 3D structure that resembles a honeycomb. CHCs were first theorized by Karfunkel and Dressler in 1992, [7] but only in 2016 were they experimentally synthetized by Krainyukova et al [8] from the deposition of vacuum-sublimated graphite.CHC's unique properties, such as high sorption and storage capacities, [9][10][11][12] membrane sieving, [13] high thermal conductivity, [14][15][16][17] or superior mechanical energy absorbing capacity [18] ), have been predicted mostly by first principles and molecular dynamics (MD) methods. The latter methods were also used to explore in detail the mechanical properties of CHCs.Using first principles, Pang et al [19] demonstrated that CHCs have high tensile strength depending on cell size and show a marked anisotropic Poisson's ratio effect.…”
mentioning
confidence: 99%
“…CHC's unique properties, such as high sorption and storage capacities, [9][10][11][12] membrane sieving, [13] high thermal conductivity, [14][15][16][17] or superior mechanical energy absorbing capacity [18] ), have been predicted mostly by first principles and molecular dynamics (MD) methods. The latter methods were also used to explore in detail the mechanical properties of CHCs.…”
mentioning
confidence: 99%